De l'animal et du végétal dans l'art Belge contemporain belge contemporain 14.09.-17.11.1985. - ATELIER 340 (Bruxelles : Atelier 340, 1985)
Alechinsky, Pierre ; Ampe, Dominique ; Baptist, Guido ; Broodthaers, Marcel ; Bruyninckx, Robert ; Buedts, Raphaël ; Callens, Mario ; Copers, Leo ; Courtois, Pierre ; Daems, Walter ; Debie, Annie ; Decoster, Jean ; De Luyck, Philippe ; De Smet, Yves ; de Villiers, Jephan ; Dupont, Veerle ; Dutrieux, Daniel ; François, Michel ; Gasparotto, Paolo ; Gheerardijn, Jean-Marie ; Heyvaert, René ; Hubert, Pierre ; Jadot, Philippe ; Jamsin, Michel ; Keil, Helène ; Lacour, Simone ; Lennep, Jacques ; Lizene, Jacques ; Lybeer, Leen ; Marga ; Mariën, Marcel ; Mass Moving ; Massart, Jean-Georges ; Michel, Johnny ; Navez, Jean-Marc ; Peeters, Dré ; Raveel, Roger ; Teller, Christine ; Van Breedam, Camiel ; Vancau, Christian ; Van Rafelghem, Paul ; Verschueren, Bob ; Volders, Francq ; Wille, Jonas
boek